2022
DOI: 10.3390/buildings12010044
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Mechanical and Durability Properties of Concrete Mixed with Silica Fume as Cementitious Material and Coal Bottom Ash as Fine Aggregate Replacement Material

Abstract: Cement production produces a high amount of carbon dioxide, which has a negative impact on the environment. By utilizing waste products instead of cement, environmental degradation can be reduced. The current study was undertaken to study the mechanical and durability performance of concrete by replacing 7.5%, 10%, and 12.5% silica fume (SF) of cement weight. Additionally, coal bottom ash (CBA) was also substituted as fine aggregates with 10%, 20%, and 30%. Compressive strength and indirect tensile strength we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Ali et al [26] studied the use of a combination of silica fume and bottom ash in concrete. They found that replacing 12.5% of cement with silica fume and 30% of fine aggregate with bottom ash resulted in a compressive strength of 38.45 MPa and a flexural strength of 4.74 MPa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al [26] studied the use of a combination of silica fume and bottom ash in concrete. They found that replacing 12.5% of cement with silica fume and 30% of fine aggregate with bottom ash resulted in a compressive strength of 38.45 MPa and a flexural strength of 4.74 MPa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has an irregular shape with large pores; thus, it affects the workability of the concrete. High water absorption due to the large pores could resulted in a bad workability in concrete [26,27].…”
Section: Bottom Ashmentioning
confidence: 99%
“…Previous research concluded that coal bottom ash can be a suitable substitute material for fine aggregate in concrete mix combined with silica fume. 30 % coal bottom ash replacement as fine aggregate along with 12.5 percent silica fume as a cement replacement achieved a maximum compressive strength of 38.45 Mpa which is almost 21% higher than the conventional concrete results [5]. In recent research it is mentioned that waste tires are recycled in four ways whole, cut, chipped or shredded and crumb.…”
Section: Introductionmentioning
confidence: 97%
“…Concrete is second to none in the list of man-made materials used in the construction industry all over the world for both residential and commercial buildings [1,2]. Its durability, aesthetic appeal, low maintenance cost and the ease with which it can be produced are the primary reasons of popularity.…”
Section: Introduction 1generalmentioning
confidence: 99%